2009
DOI: 10.1093/hmg/ddp522
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence that raised sex hormone binding globulin (SHBG) levels reduce the risk of type 2 diabetes

Abstract: Epidemiological studies consistently show that circulating sex hormone binding globulin (SHBG) levels are lower in type 2 diabetes patients than non-diabetic individuals, but the causal nature of this association is controversial. Genetic studies can help dissect causal directions of epidemiological associations because genotypes are much less likely to be confounded, biased or influenced by disease processes. Using this Mendelian randomization principle, we selected a common single nucleotide polymorphism (SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
162
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(175 citation statements)
references
References 40 publications
11
162
1
1
Order By: Relevance
“…This principle of Mendelian randomisation has been used to assess the causal relationship between several related metabolic phenotypes, e.g. C-reactive protein and heart disease [3], and sex hormone-binding globulin levels and diabetes [4]. Most recently, studies have combined multiple risk variants in a 'genetic risk score' to provide more power compared with individual variants.…”
Section: Introductionmentioning
confidence: 99%
“…This principle of Mendelian randomisation has been used to assess the causal relationship between several related metabolic phenotypes, e.g. C-reactive protein and heart disease [3], and sex hormone-binding globulin levels and diabetes [4]. Most recently, studies have combined multiple risk variants in a 'genetic risk score' to provide more power compared with individual variants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, rs6259, rs6257 and rs1799941 polymorphisms in the SHBG gene were strongly associated with SHBG levels and type 2 diabetes (Zeggini et al, 2008;Perry et al, 2010). However, there was no evidence that this variant is associated with diabetes-related intermediate traits, including several measures of insulin secretion and resistance (Perry et al, 2010).…”
Section: The Polymorphisms Of the Shbg Genementioning
confidence: 99%
“…Moreover, polycystic ovarian syndrome was associated with higher risk of type 2 diabetes and insulin resistance in women (Dunaif, 1995). Recent studies have demonstrated that higher levels of circulating sex hormone binding protein (SHBG) were associated with reduce risk of type 2 diabetes (Ding et al, 2009;Perry et al, 2010). In addition, rs6259, rs6257 and rs1799941 polymorphisms in the SHBG gene were strongly associated with SHBG levels and type 2 diabetes (Zeggini et al, 2008;Perry et al, 2010).…”
Section: The Polymorphisms Of the Shbg Genementioning
confidence: 99%
See 1 more Smart Citation
“…Глобулін, що зв'язує статеві стероїди (ГЗСС), являє собою глікопротеїд, який регулює біодоступність андрогенів шляхом зв'язування статевих стероїдів [9,33,34]. Дослідження показали, що зниження рівня сироваткового ГЗСС асоційоване з ризиком розвитку СПКЯ у жінок, а також цукрового діабету (ЦД) 2 типу у чоловіків і жінок [22,17,35,36].…”
unclassified